2018
DOI: 10.1016/j.envpol.2017.10.074
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the effects of polychlorinated biphenyls on cetacean populations through impacts on immunity and calf survival

Abstract: The potential impact of exposure to polychlorinated biphenyls (PCBs) on the health and survival of cetaceans continues to be an issue for conservation and management, yet few quantitative approaches for estimating population level effects have been developed. An individual based model (IBM) for assessing effects on both calf survival and immunity was developed and tested. Three case study species (bottlenose dolphin, humpback whale and killer whale) in four populations were taken as examples and the impact of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(55 citation statements)
references
References 68 publications
0
55
0
Order By: Relevance
“…Anthropogenic activities included those that previous studies have indicated may adversely affect the distribution, health and reproductive status of humpback whales. These include ocean acidification anomalies, fishing intensity (representing potential for entanglement), pollution, oil and gas platforms (as a proxy for oil and gas industry activity impacting water quality and generating noise), shipping (potential for vessel strikes and generating noise), sea‐level rise (SLR) and SST anomalies (Bettridge et al, ; Bezamat, Wedekin, & Simões‐Lopes, ; Blair, Merchant, Friedlaender, Wiley, & Parks, ; Dunlop et al, ; Hall et al, ; Ilyina, Zeebe, & Brewer, ; Laist, Knowlton, Mead, Collet, & Podesta, ; Moore, ; Rosenbaum et al, ). The CUI score was calculated per grid cell as follows:CUIi=false∑j=1nDi×Si×ui,jwhere n is the number of anthropogenic activities, D i is the normalized, log‐transformed intensity value of an activity at location (grid cell) i , S i is the predicted distribution of humpback whale breeding habitat produced by the Maxent model at location i , and u i,j is the impact weight score for activity j on humpback whales at location i (Halpern et al, ; Maxwell et al, ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Anthropogenic activities included those that previous studies have indicated may adversely affect the distribution, health and reproductive status of humpback whales. These include ocean acidification anomalies, fishing intensity (representing potential for entanglement), pollution, oil and gas platforms (as a proxy for oil and gas industry activity impacting water quality and generating noise), shipping (potential for vessel strikes and generating noise), sea‐level rise (SLR) and SST anomalies (Bettridge et al, ; Bezamat, Wedekin, & Simões‐Lopes, ; Blair, Merchant, Friedlaender, Wiley, & Parks, ; Dunlop et al, ; Hall et al, ; Ilyina, Zeebe, & Brewer, ; Laist, Knowlton, Mead, Collet, & Podesta, ; Moore, ; Rosenbaum et al, ). The CUI score was calculated per grid cell as follows:CUIi=false∑j=1nDi×Si×ui,jwhere n is the number of anthropogenic activities, D i is the normalized, log‐transformed intensity value of an activity at location (grid cell) i , S i is the predicted distribution of humpback whale breeding habitat produced by the Maxent model at location i , and u i,j is the impact weight score for activity j on humpback whales at location i (Halpern et al, ; Maxwell et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Shipping (strikes and associated noise), entanglement in fishing gear, and oil platforms (and operations associated with hydrocarbon industry activities) are of greatest concern to humpback whales. These activities are known to impact humpback whales either directly or indirectly through changes in prey availability and distribution, decrease in fitness and/or decreases in habitat quality and area, and even risk of mortality (Bettridge et al, 2015;Bezamat et al, 2015;Blair et al, 2016;Brierley et al, 2002;Cerchio, Strindberg, Collins, Bennett, & Rosenbaum, 2014;Dunlop et al, 2016;Findlay et al, 2006;Hall et al, 2018;Kawaguchi et al, 2011;Moore, 2009;Richardson, Greene, Malme, & Thompson, 1995).…”
Section: Overlap With Cumulative Anthropogenic Activitiesmentioning
confidence: 99%
“…Baleen whales, including minke whales, typically feeding on lower trophic levels than toothed whales, have comparatively lower blubber POP concentrations (Elfes et al, 2010). Nonetheless POPs may have adverse effects on health and reproduction of populations of both species groups (Moon et al, 2010;Hall et al, 2018), especially in combination with other stressors (Côté et al, 2016).…”
Section: Marine Litter and Chemical Pollutionmentioning
confidence: 99%
“…It is common in toxicological risk assessments (including humans) to assemble a convincing weight of evidence that incorporates dose response studies in sentinel or surrogate species (such as laboratory rodents) (Ross & Birnbaum, ). Our supplementary text provides a detailed discussion on the topic and refers to a previous model description paper for additional details (Hall et al, ). While mink ( Mustela lutreola or Neovison vison ) may well possess different sensitivity to PCBs than killer whales, the general conservation of toxicological mechanisms and modes of action for PCBs across taxa provides a foundational basis for human and wildlife toxicology, with mink being a widely accepted surrogate species in marine mammal toxicology (see Hall et al, and references therein).…”
Section: Surrogate Speciesmentioning
confidence: 99%
“…Our supplementary text provides a detailed discussion on the topic and refers to a previous model description paper for additional details (Hall et al, ). While mink ( Mustela lutreola or Neovison vison ) may well possess different sensitivity to PCBs than killer whales, the general conservation of toxicological mechanisms and modes of action for PCBs across taxa provides a foundational basis for human and wildlife toxicology, with mink being a widely accepted surrogate species in marine mammal toxicology (see Hall et al, and references therein). In the first model iteration, Hall et al () assessed a unique data set of PCB calf toxicity in bottlenose dolphins and found a much greater calf mortality rate at lower maternal blubber PCB concentrations in the dolphins compared to the mink dose‐response data used in the current model implementation.…”
Section: Surrogate Speciesmentioning
confidence: 99%